2020
DOI: 10.2196/23315
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value of Data and Analytics for Health Care Providers: Hermeneutic Systematic Literature Review

Abstract: Background The benefits of data and analytics for health care systems and single providers is an increasingly investigated field in digital health literature. Electronic health records (EHR), for example, can improve quality of care. Emerging analytics tools based on artificial intelligence show the potential to assist physicians in day-to-day workflows. Yet, single health care providers also need information regarding the economic impact when deciding on potential adoption of these tools. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…Studies that provided insights into the economic value and practical applications of AI and Data Analytics in various business sectors were also included. This was in line with the approach taken by Von Wedel and Hagist (2020), who conducted a hermeneutic systematic literature review focusing on the economic value of data and analytics in healthcare, demonstrating the importance of including studies assessing technological innovations' economic impact. Exclusion criteria were applied to filter out studies that did not directly relate to the core themes of AI, Data Analytics, and BI.…”
Section: Criteria For Inclusion and Exclusion Of Sourcessupporting
confidence: 73%

Business Intelligence Transformation Through Ai and Data Analytics

Emmanuel Osamuyimen Eboigbe,
Oluwatoyin Ajoke Farayola,
Funmilola Olatundun Olatoye
et al. 2023
Eng. sci. technol. j.
“…Studies that provided insights into the economic value and practical applications of AI and Data Analytics in various business sectors were also included. This was in line with the approach taken by Von Wedel and Hagist (2020), who conducted a hermeneutic systematic literature review focusing on the economic value of data and analytics in healthcare, demonstrating the importance of including studies assessing technological innovations' economic impact. Exclusion criteria were applied to filter out studies that did not directly relate to the core themes of AI, Data Analytics, and BI.…”
Section: Criteria For Inclusion and Exclusion Of Sourcessupporting
confidence: 73%

Business Intelligence Transformation Through Ai and Data Analytics

Emmanuel Osamuyimen Eboigbe,
Oluwatoyin Ajoke Farayola,
Funmilola Olatundun Olatoye
et al. 2023
Eng. sci. technol. j.
“…EHR can make it easier for researchers to access and aggregate clinical data. The application of EHR in clinical nursing can reduce medication errors, improve patient medication compliance, and reduce nurses' work burden ( 2 , 4 ). In addition, researchers are paying more and more attention to the potential of EHR.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare providers reported that Electronic Healthcare Records (EHR) systems help enhance communication, eliminate redundancy in the delivery of care, and allow quick access to critical information (Silow-Carroll et al, 2012;Zhang et al, 2019). As a result, EHR systems enable providers to become more efficient in delivering care and reduce unnecessary hospital stays (Thompson et al, 2006;Von Wedel & Hagist, 2020). Some healthcare practitioners are concerned that reducing hospital length of stay (LOS) may lead to higher rates of readmissions and mortality; however, recent studies show that there is no significant correlation between LOS and readmission and mortality rates and that a longer LOS does not necessarily mean better quality of care (Kaboli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%